A Clash of Social Classes in Margarita Morris Goodbye to Budapest (2019) - Dimas Hendra Pramudya (Journal Albion : Journal of English Literature, Language, and Culture, 2022)
Goodbye to Budapest (2019) is a novel by Margarita Morris. The novel is set in Hungary in the 1950s during the Stalinist regime. The novel portrays the sufferings of lower-class people caused by the regimes cruelty. On the other side, the novel also briefly portrays the good life of nomenklaturas or the upper-class people who supported the regime. Dissatisfied with the regimes cruelty, the lowerclass people rose against the government, including the nomenklaturas that were close to the government. Thus, the nomenklaturas which were once being upper-class became the most hated social class.Keywords: social class; society; revolution; Hungarian Revolution.